(untitled) (The Pretoria Student Law Review, 2021)
This article seeks to examine the doctrine of constitutional avoidance and assess whether it has had an impact on the protection of Human Rights in BotswanaBotswana through the courts. This article will begin with the definition the doctrine of constitutional avoidance. This will be followed by an overview of Botswana’s constitution and its Human Rights framework. The article will then go on to discuss the application of constitutional avoidance in Botswana, highlighting some case law that has been instrumental in the development of the doctrine of constitutional avoidance.